A ANAK ANGKAT DALAM PERSPEKTIF HUKUM ISLAM: KEBIJAKAN DAN TANTANGAN - Burhanuddin Burhanuddin (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
ABSTRACT The study examines the concept and implementation of child abduction (kafalah) from the perspective of Islamic law, as well as the policies and challenges it faces in various Islamic-law-based countries. Kafalah, as a form of protection and authorization of children without changing nasab, has a strong foundation in the Quran and Hadith, and is interpreted by scholars from various Islamic mazhab. The study uses qualitative methods with literature study approaches, analysis of legal documents, and interviews to understand how these concepts are applied in different countries, as well as to identify challenges and provide relevant recommendations. The results show that although the basic principles of kafalah are similar throughout the Muslim world, their implementation varies greatly depending on the legal, social, and cultural context of each country. The main challenges faced include consistency in the interpretation of the law, protection of children's rights, abuse of the system, administrative difficulties, and social acceptance of adopted children. Case studies from countries such as Malaysia, Saudi Arabia, and Indonesia provide insights into the range of existing approaches and practices, as well as the unique challenges faced in each context. The study's findings emphasize the importance of harmonizing religious values and protecting children's rights, as well as the need for inclusive policies and public education to enhance social acceptance of adopted children. The study's findings emphasize the importance of harmonizing religious values and protecting children's rights, as well as the need for inclusive policies and public education to enhance social acceptance of adopted children. The proposed recommendations include harmonization of Islamic law with international standards on children's rights, raising public awareness, cross-sectoral cooperation, upgrading legal infrastructure, and advocacy of child rights protection at the national and international levels. Keywords: Kafalah, Islamic law, child protection